2014
DOI: 10.1177/0961203314532563
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disorders in systemic lupus erythematosus. Does vitamin D play a role?

Abstract: We found a role for vitamin D in sleep quality of SLE patients. Further studies are warranted to confirm these results and to find possible mechanisms of action.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 13 publications
2
15
0
Order By: Relevance
“…To the best of our knowledge, this is the first study to analyze the association between serum levels of vitamin D and sleep quality in HD patients. We found that low serum levels of vitamin D were significantly associated with sleep disturbance in HD patients, which is similar to the findings of previous studies in elderly adults and patients with SLE [ 12 , 13 , 14 ]. Our finding might have important implications in providing novel proposals for the prevention and treatment of sleep disturbance in HD patients.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…To the best of our knowledge, this is the first study to analyze the association between serum levels of vitamin D and sleep quality in HD patients. We found that low serum levels of vitamin D were significantly associated with sleep disturbance in HD patients, which is similar to the findings of previous studies in elderly adults and patients with SLE [ 12 , 13 , 14 ]. Our finding might have important implications in providing novel proposals for the prevention and treatment of sleep disturbance in HD patients.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, increasing clinical studies have shown that low serum levels of vitamin D are associated with poorer sleep, including low sleep efficiency and short sleep duration, in non-HD subjects, suggesting a potential role for vitamin D in maintaining healthy sleep [ 12 , 13 ]. Similarly, a significantly correlation between vitamin D levels and sleep quality has been found in patients with systemic lupus erythematosus (SLE) [ 14 ]. Recent uncontrolled clinical trials of vitamin D supplements in patients with sleep problems have reported improved sleep quality with higher levels of supplemental vitamin D [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…6 Furthermore, it also associated with the quality of sleep. 12 On the contrary, vitamin D intake has been suspected as a risk factor for development of systemic lupus erythematosus in women, however, this has been disproved by Costenbader et al 13 In the Kingdom of Bahrain, a population-based study has confirmed a high prevalence of VDD in healthy subjects, especially in females, and that showed a seasonal variation. 14 Nevertheless, vitamin D status in Bahraini patients with SLE has not been investigated before.…”
Section: Introductionmentioning
confidence: 99%
“…In an observational study of 60 patients who took vitamin D 3 , an inverse relationship between the 25-(OH) 3 level and fatigue score was identified [101]. Apart from fatigue, the vitamin D level was found to be related to sleep quality in the patients with SLE [102]. With the use of the Pittsburgh Sleep Quality Index, a retrospective study of 60 SLE patients revealed a significant relationship between a low serum vitamin D level and poor sleep quality [102].…”
Section: Vitamin D and Its Major Extra-musculoskeletal Impactsmentioning
confidence: 99%
“…Apart from fatigue, the vitamin D level was found to be related to sleep quality in the patients with SLE [102]. With the use of the Pittsburgh Sleep Quality Index, a retrospective study of 60 SLE patients revealed a significant relationship between a low serum vitamin D level and poor sleep quality [102]. …”
Section: Vitamin D and Its Major Extra-musculoskeletal Impactsmentioning
confidence: 99%